2022
DOI: 10.3389/fmats.2022.1018815
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels for the treatment of radiation-induced skin and mucosa damages: An up-to-date overview

Abstract: Radiation-induced damages are difficult to heal than normal wounds. This is because radiation therapy could lead to an imbalanced inflammatory response, oxidative stress response, lack of angiogenesis, and a high risk of bacterial infection, which are considered to be the greatest challenges in radiation-induced damages treatment. Hydrogels are semi-occlusive and are composed of complex hydrophilic polymers with a higher water content. Due to their excellent mechanical and biochemical property (such as adhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…The choice of dressing can be traditional, but it is suggested that hydrocolloid/hydrogel-based wound covering be considered. 16,17 These dressings provide gentle adhesion, compared to adherence dressings, and water vapor transmission, that can augment wound infection control “and perform autolytic debridement of necrotic tissue by piggybacking on antibiotics or anti-inflammatory drugs during the inflammatory phase. In the proliferative phase, hydrogel dressings can promote vascular regeneration and fibroblast proliferation by releasing growth factors and degradation of bioactive materials.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of dressing can be traditional, but it is suggested that hydrocolloid/hydrogel-based wound covering be considered. 16,17 These dressings provide gentle adhesion, compared to adherence dressings, and water vapor transmission, that can augment wound infection control “and perform autolytic debridement of necrotic tissue by piggybacking on antibiotics or anti-inflammatory drugs during the inflammatory phase. In the proliferative phase, hydrogel dressings can promote vascular regeneration and fibroblast proliferation by releasing growth factors and degradation of bioactive materials.…”
Section: Resultsmentioning
confidence: 99%
“…3,19 Novel approaches gaining attention include functional hydrogels with complex properties, photoresponsive hydrogels combined with light-based therapy, and hydrogels integrated with biopolymers. 3,20 Patients with osteoradionecrosis should undergo surgical treatment with the primary goals of eliminating infection, excising all damaged tissue, and providing stability to the chest wall during reconstruction. Surgical intervention should involve the removing infected tissue and skin affected by radiation to facilitate proper healing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study evaluated the biological activity of IFI6 in wound healing using these hydrogels for skin regeneration, assessing cell proliferation, migration, and angiogenesis. This research highlights the significant potential of IFI6-based treatments in managing and healing RISI, advocating for further investigation into its broader therapeutic applications (as shown in Figure 9 b) [ 115 , 116 , 117 ].…”
Section: Brief Application Of Hydrogelsmentioning
confidence: 98%